Crop-livestock interaction effect on soil quality and maize yield in northern Ghana - Rahman, N.A.; Larbi, Asamoah; Opoku, A.; Tetteh, F.M.; Hoeschle-Zeledon (Wiley, 2019)
Keeping livestock overnight on fallow arable lands (Corralling) is a traditional method of soil fertility amendment in West Africa. However, there is limited quantitative data on the interaction effects of stocking density of sheep and goats corralling (SDSG), maize plant density (MPD) and nitrogen fertilizer rate (NFR) on soil quality and yield of maize. A 2-yr study was conducted to determine the interaction effects of three SDSG (0, 70, and 140 head ha–1), three MPD (66,667, 100,000, and 133,333 plants ha–1) and three NFR (0, 60, and 90 kg ha–1 N) on soil quality index (SQI) and maize yield in northern Ghana. The study was conducted using a split-split plot experiment replicated on eight farms. An adult sheep or goat was corralled in an area of 4 m2 and 1 m2 for the 70 and 140 head ha–1 SDSG respectively for five nights during the dry seasons of 2014 and 2015 cropping seasons. Principal component and correlation matrix analysis were used to select minimum data set for SQI. The SQI for sheep and goats corralling increased by 51% compared with the control. The SDSG×MPD, SDSG×NFR and MPD×NFR interactions were significant on maize grain and biomass yields. The results suggest that, small-scale maize-livestock farmers could use either SDSG of 70 head ha–1 with 90 kg ha–1 NFR or SDSG of 140 head ha–1 with 60 kg ha–1 NFR and MPD at 133,333 plants ha–1 to increase grain yield on Ferric lixisols in northern Ghana and similar ecologies in West Africa.